794. Infectivity of Smear-Positive Pulmonary TB After 2 Weeks of Rifampicin-based Anti-Tuberculous Therapy. (26th November 2018) - Alhowady, Faraj; Elmaki, Nada; Ali, Maisa; Husain, Ahmad; Al-Maslamani, Muna; Alsuwaidi, Zubaida; Mohamed, Mahmoud; Alsoub, Hussam
Abstract: Background: Pulmonary tuberculosis (TB) remains one of the leading infectious causes of morbidity and mortality worldwide. Most data showed that infectiousness of pulmonary TB diminishes rapidly after 2 weeks of effective anti-tuberculous therapy and the bacilli seen in the smear after 2 weeks are most likely nonviable. We aim to assess this hypothesis by doing sputum culture after 2 weeks of therapy to assess the viability of the bacilli in the smear. Methods: A prospective cohort study was conducted on patients admitted to Communicable Disease Centre (CDC), Qatar with smear positive pulmonary tuberculosis during the period November 2013–November 2014. We repeated sputum smear and culture after 2 weeks of rifampicin based regimen to assess the infectivity. Demographic and clinical characteristics of patients was evaluated and compared with smear and culture conversion rate. Results: Ninety-five cases were included in the study. All had sputum smear and culture after 2 weeks of supervised rifampicin based therapy (Table 1). Sputum culture at two weeks of treatment was positive in 91 cases (95.7%) and only four cases were culture negative after 2 weeks. Demographic and clinical characteristics were compared with the culture status after 2 weeks, found Patient from Indian subcontinent and symptoms duration more than 1 month are less likely to clear infection after 2 weeks with P -value 0.01 and 0.009, respectively (Table 2). The calculated mean for sputum smear and culture conversion rate was 4 and 8 weeks, respectively. The presence of cough and the duration of symptoms were associated significantly with rapid sputum conversion ( P < 0.05); however, the presence of cavity on CXR had no statistical significant effect (Table 3). Conclusion: Majority of our patients in the study have positive TB culture after two weeks of rifampicin based anti-tuberculosis therapy. So, discontinuation of the isolation after 2 weeks of treatment assuming that bacilli in the smear are nonviable may not be safe. Disclosures: All authors: No reported disclosures.